Europe's monetary union. - Feldstein, Martin (1992)
Aruges that the European Community should abandon its plans for monetay union since a monetary union is not a prerequisite of a single market for goods and services. Points out that an artificially contrived economic and monetary union might actually reduce the volume of trade among member countries and would reduce the average level of unemployment over time.